INVESTIGATING THE INFLUENCE OF LONELINESS ON INTERNET ADDICTION AND BURNOUT IN ACCOUNTANTS - Clarkson, Julian (Ayden International Journal of Banking, Finance and Technology, 2024)
This empirical study examines the mediating role of loneliness between internet addiction and burnout levels among accountants in Turkiye, using the partial least squares structural equation model (PLS-SEM). The survey method was used to gather 231 responses from accountants, and the results showed that loneliness partially mediated the relationship between internet addiction and burnout levels, specifically emotional exhaustion, depersonalization, and reduced personal accomplishment levels. This study contributes to the existing literature by exploring the mediating effect of loneliness on the relationship between internet addiction and burnout levels in the context of accounting. The findings provide valuable insights for employers and policymakers in developing strategies to manage the negative impact of internet addiction on burnout levels among accountants.